Shrimp Aquaculture in Inland Saline Waters of Haryana: A Step towards Sustainable Aquafarming - M. G., Ragunathan; Yadav, Ankesh; J., Jayanthi; Basu, Kundan; Malakondaiah, Suresh (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The sustainability of many rural communities is threatened by the rise in inland salinity brought on by human activity, which has significant economic, social, and environmental effects. As aquaculture becomes more and more in demand, new production technologies are being developed. Inland saline water shrimp farming, defined here as land-based aquaculture using saline groundwater, occurs in various Indian states, including Haryana, Punjab, and Rajasthan and has a substantial influence on the socioeconomic progress of the states. Commercial aquaculture has risen in places like Haryana due to the enormous potential for raising a wide range of shrimp and shellfish in inland saline groundwater (ISGW). The most often raised shrimp in Haryana, the Pacific whiteleg shrimp (Litopenaeus vannamei), is one of the most frequently utilized aquaculture species. Due to its increased capacity to utilise low protein diets, faster growth and survival rates, tolerance to a range of environmental changes, and high disease resistance, Litopenaeus vannamei is acknowledged as one of the desirable candidate species for inland saline aquaculture. Farmers in the area, however, frequently deal with issues including disease outbreaks, managing water quality, and the requirement for specialist feed that is tailored to the particular conditions of inland saltwater environments. Sustainable production depends on best practices such routinely checking the quality of the water, implementing biosecurity precautions, and adding probiotics to feed. Despite these obstacles, predictions show that shrimp farming in Haryana has the potential to grow considerably with further study, technology developments, and government support. This would boost the state's economy, create new job opportunities, and support environmental sustainability. The current article focuses on the difficulties and restrictions that aquaculture in Haryana currently faces as well as it covers a number of methods for choosing the right soil and managing the water supply for inland saline aquaculture. Finally, the article also addresses how Haryana aquaculture may have access to new markets that will increase its overall productivity and sustainability as a result of rising inland salinity brought on by human activities.